👤

a+b+c=94 a=26 b=9>a c=?

Răspuns :

a=26                                                                                                              b=9>a rezulta ca b=26+9=35                                                                             a+b+c=94                                                                                                       26+35+c=94                                                                                                   61+c=94                                                                                                          c=33
a=26 b=26+9 b=35 26+35=61 94-61=33 c=33